Supportless Pt-ionomer hybrid porous nanofibrous networks with self-regulated water management for polymer electrolyte fuel cells. (June 2022) - Sun, R.; Xia, Z.; Zhang, Z.; Xu, X.; Jing, F.; Wang, S.; Sun, G.
Abstract: Water management within the electrode architecture restrains the performance and dynamic stability of polymer electrolyte fuel cells (PEFCs), especially with the reduction of precious electrocatalyst loading. Local mass transport at the catalyst-ionomer interphase crucially depends on the water uptake of the ionomer layers, which could be optimized via balancing electrode flooding and draining during the dynamic change of current and humidification. Herein this work, supportless platinum-ionomer hybrid porous nanofibrous are constructed via a new method combined with electrospinning and electrochemical etching. Ascribing to the hierarchical architecture of continuous platinum-ionomer nano-dendrites and fibrous networks, only 17.8% maximum power density deviation under varied cathode humidity is observed in the porous nanofibrous cathode, compared to 160% deviation for traditional one. Such self-regulated water management within this electrode is achieved due to stable interfacial layer constructed under working circumstance. This presented work could provide alternative thoughts on mass transport issues affected by nanoscale interfacial structures and demonstrate an efficient design of electrode architecture with better performance and dynamic stability for polymer electrolyte fuel cells. Graphical abstract: Supportless Pt-ionomer porous nanofiber electrodes are constructed via an electrochemical etching assisted electrospinning approach with a unique self-regulated water management. Image 1 Highlights: Supportless platinum (Pt)-ionomer porous nanofibrous network is constructed. Unique special interfaces are formed with Perfluorosulfonic Acid (PFSA) covered Pt nano-dendrite matrix. A great reduction of oxygen transport resistance is found in this new electrode. Only 17.8% of Pmax change is observed under remarkably varied humidity. Such self-regulated water management within Pt/PFSA porous nanofibrous electrode is elucidated.